A Proposed Supply Chain Management Model for Teacher Education Institutions: A Structural Equation Modeling - Darwin Pascua Paguio; Md. Mamun Habib (International Journal of Supply Chain Management, 2017)
The effects of globalization on higher education bring rapid developments, thereby, foreseeing changes within teaching and learning systems and producing an information-based society. The higher education system has been facing major challenges, especially in matching its outcomes to the market (society) needs. These challenges are increasing as the job market becomes more globally competitive. This study proposed a Supply Chain Management (SCM) model for Teacher Education Institutions (TEIs). The study utilized cross-sectional, explanatory research design and was participated in by 863 respondents composed of administrators, faculty, students and graduates selected through purposive sampling using partial least square structural equation modeling (PLS-SEM). Results from instruction model show that the program establishment is the most significant factor for both instruction development and instruction assessment in producing high level of quality graduates. Results from research model show that the program establishment in research development and TEIs culture in research assessment are the most significant factor in producing relevant research output. For the extension output, program establishment is the most significant factor in extension development while in extension assessment, faculty capabilities and facilities are the most significant factors in producing service oriented professionals. The model was called Productivity and Advancement of Graduates through a Unified and Innovative Outputs Instruction, Research and Extension or PAGUIO-INREX Model. This model emphasizes the importance of the trifocal function of higher education to the formation of productive and competent graduates of Teacher Education Institutions, who in turn, can contribute to the progress and development of the country.